2004
DOI: 10.1007/s00535-003-1240-6
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effects of single intravenous doses of omeprazole and famotidine on intragastric pH

Abstract: In Helicobacter pylori-negative healthy male subjects, an intravenous dose of 20 mg famotidine increased intragastric pH more rapidly than intravenous omeprazole 20 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Although acid inhibition by PPI or H 2 RA treatment differs between H. pylori- negative and H. pylori- positive subjects, few reports have discussed changes in pH during the early phase or the increasing pH value in H. pylori- positive patients [49, 53]. We previously reported the presence of differences between PPI and H 2 RA with regard to their potency and time to acid inhibition in healthy H. pylori- positive subjects.…”
Section: Acid Inhibitory Drugs and Intragastric Phmentioning
confidence: 95%
See 1 more Smart Citation
“…Although acid inhibition by PPI or H 2 RA treatment differs between H. pylori- negative and H. pylori- positive subjects, few reports have discussed changes in pH during the early phase or the increasing pH value in H. pylori- positive patients [49, 53]. We previously reported the presence of differences between PPI and H 2 RA with regard to their potency and time to acid inhibition in healthy H. pylori- positive subjects.…”
Section: Acid Inhibitory Drugs and Intragastric Phmentioning
confidence: 95%
“…Although PPIs inhibit gastric acid secretion more potently than H 2 RAs overall, PPIs have the disadvantage of exerting relatively weak acid inhibition in the early phase after initial dosing compared with H 2 RAs, which exert their inhibitory effects within a couple of hours of dosing [53]. Indeed, an intravenous infusion of famotidine 20 mg increases pH over 4 h more rapidly than omeprazole 20 mg in H. pylori- negative subjects [54, 55].…”
Section: Acid Inhibitory Drugs and Intragastric Phmentioning
confidence: 99%
“…Because PPI can block only activated proton pomp, gastric pH does not reflect blood concentration of omeprazole directory. Our previous manuscripts [13-15] reported that after PPI administration, intragastric pH value raise showing up and down.…”
Section: Discussionmentioning
confidence: 99%
“…In our study design, we did not try to measure the changes of intragastric pH before and after administration of gastric acid suppressants, but we have previously reported that adequate acid suppression and elevation of the intragastric pH is achieved in the early post-administration phase after a single intravenous administration of gastric acid suppressants 41,42. Although intravenous famotidine had a more rapid onset of action and exerted stronger inhibition of intragastric acid secretion than intravenous omeprazole or lansoprazole in our previous study, there were no significant differences in the gastric emptying rate between the famotidine and omeprazole administration groups in the present study.…”
Section: Discussionmentioning
confidence: 99%